СУДЬЯ КАК ИССЛЕДОВАТЕЛЬ ИСТОРИЧЕСКОЙ ПАМЯТИ - А.А. Васильев; М.А. Боловнев (Российско-азиатский правовой журнал)
The article provides a comprehensive analysis of the role of education in the formation of an individual'slegal consciousness. The author examines modern approaches to legal education, identifying their strengthsand weaknesses in a changing socio-cultural and legal landscape. Special attention is paid to the ability ofeducational systems to adapt to new challenges, such as globalization, technology development and thestrengthening of transnational legal processes. The article offers a critical look at existing teaching methods  and their compliance with the needs of future specialists entering the legal field. The author calls for thereform of educational programs, paying special attention to the development of critical thinking and theability to adapt to complex and dynamic legal situations.В статье на основе общенаучных, исторических и юридических методов проведения исследований, а также примеров исторических судебных процессов, в том числе реабилитационного характера, устанавливается особая роль судей как субъектов, формирующих историю. При этом сформированная судами историческая память играет весомую роль для будущих поколений. Отмечается, что,обладая особой достоверностью и юридической силой, судебные акты становятся источниками получения знаний обществом, а также предметом исследования историков.